If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9 + 2z + 9z = -1 + 10z Combine like terms: 2z + 9z = 11z 9 + 11z = -1 + 10z Solving 9 + 11z = -1 + 10z Solving for variable 'z'. Move all terms containing z to the left, all other terms to the right. Add '-10z' to each side of the equation. 9 + 11z + -10z = -1 + 10z + -10z Combine like terms: 11z + -10z = 1z 9 + 1z = -1 + 10z + -10z Combine like terms: 10z + -10z = 0 9 + 1z = -1 + 0 9 + 1z = -1 Add '-9' to each side of the equation. 9 + -9 + 1z = -1 + -9 Combine like terms: 9 + -9 = 0 0 + 1z = -1 + -9 1z = -1 + -9 Combine like terms: -1 + -9 = -10 1z = -10 Divide each side by '1'. z = -10 Simplifying z = -10
| -3d=-8-7d | | 2w+6=-2-10 | | 2(x-1)-3(3x+2)+4(x+2)=0 | | -2y+5+3y=5y+5 | | .5b+4=20 | | -10-5g=8+4g | | 5(2l+3)=95 | | 10j+2=9j+10 | | (x+19)=(7x-8) | | q=9+2q | | 5k+9=4K | | -2k+4m=-9 | | 10u-3=9u-6 | | 7f-8=6f | | 5x+y+4x-y=360 | | -0.146x^2+0.96x+7.5=0 | | 4x-y=55 | | s=2cos(0) | | -26+7p=2(7p-6) | | -8(8k-8)-3=-6k+3 | | (3x-1)(2x-5)=(3x-1)(x+2) | | 4n+27= | | 5n+18= | | 6=3*-9+21 | | 6(-2-6n)-4n=268 | | 2=4x-3+5x-8-6x-3 | | 147=-1-4(3+5m) | | (21x+2)= | | -2-6n=-4(1+2n) | | x+y=5y=3 | | 3+4t=4y+3 | | 9a-2a=8b-4b |